2020
DOI: 10.1016/j.cgh.2020.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Significance of Portal Vein Thrombosis in Patients With Cirrhosis and Acute Decompensation

Abstract: This article has an accompanying continuing medical education activity, also eligible for MOC credit, on page e135. Learning Objective-Upon completion of this activity, successful learners will be able to list the criteria for diagnosis of cirrhosis with acute decompensation; list at least 1 independent risk factor for portal vein thrombosis in patients with cirrhosis and acute decompensation; list 3 indicators for acute decompensation in patients with cirrhosis; and know the impact of portal vein thrombosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 20 publications
5
71
2
1
Order By: Relevance
“…In this study, causes of PVT were heterogeneous (1/3 being related to splenectomy or partial splenic embolisation) and liver disease was significantly less severe in the PVT group. 62 In another prospective study there was no correlation between development of PVT and variceal bleeding or mortality but progressive PVT did correlate with worsening ascites. 9 The fact that, at time of diagnosis, PVT is often asymptomatic 63 has also been used as an argument against a major role of PVT in worsening outcomes in cirrhosis.…”
Section: Clinical Consequences Of Pvt In Cirrhosismentioning
confidence: 93%
See 1 more Smart Citation
“…In this study, causes of PVT were heterogeneous (1/3 being related to splenectomy or partial splenic embolisation) and liver disease was significantly less severe in the PVT group. 62 In another prospective study there was no correlation between development of PVT and variceal bleeding or mortality but progressive PVT did correlate with worsening ascites. 9 The fact that, at time of diagnosis, PVT is often asymptomatic 63 has also been used as an argument against a major role of PVT in worsening outcomes in cirrhosis.…”
Section: Clinical Consequences Of Pvt In Cirrhosismentioning
confidence: 93%
“…64 Similarly, in the previously mentioned large retrospective cohort of 2,597 patients admitted with acute decompensation, patients with PVT were more likely to have been admitted with variceal haemorrhage compared to those without PVT. 62 Moreover, in patients with variceal bleeding, PVT was found to be independently associated with a higher risk of failure to control acute variceal bleeding, rebleeding and short-term mortality [65][66][67] Further arguments on the issue come from studies that have correlated the response of PVT to treatment, mostly anticoagulation, and patient outcome. In this regard, it has been shown that successful treatment of PVT decreases variceal pressure 68 and may reduce the risk of decompensation.…”
Section: Clinical Consequences Of Pvt In Cirrhosismentioning
confidence: 99%
“…In another two cohort studies that mainly included patients with Child–Pugh B or C cirrhosis, the 1‐year cumulative incidence of PVT was 16.4% and 17.9% 5,6 . A large‐scale multicenter retrospective study in China demonstrated that cirrhotic patients with acute decompensation events had a significantly higher prevalence of PVT than those without (9.36% vs 5.24%) 7 . Taken together, PVT is a common complication of liver cirrhosis and is associated with the severity of liver dysfunction.…”
Section: Epidemiologymentioning
confidence: 99%
“…[ 10 , 18 , 19 , 21 , 23 , 25 ] In patients with cirrhosis, the development of PVT is associated with the severity of liver disease at baseline, but does not follow the recent progression of liver disease in the study by Nery. Zhang [ 30 ] reported a prevalence of nonmalignant PVT in patients with acute decompensation (AD) of 9.36%, which was significantly higher than in patients without AD (5.24%). Because PVT might possibly progress or exacerbate portal hypertension-related variceal bleeding, PVT potentially increases the risk of death by contributing to the development of AD.…”
Section: Discussionmentioning
confidence: 99%